2003
DOI: 10.4040/jkan.2003.33.1.95
|View full text |Cite
|
Sign up to set email alerts
|

A Correlation Study of Perceived Importance of Nursing Interventions with Performance Frequency in Psychiatric Nursing Units Using the 3th NIC

Abstract: In conclusion, nurses in clinical settings were found to perform less than perceive its importance. Therefore, further researches are needed to identify factors related to impede and develop strategies to improve the performance of nursing interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
2
0
3
Order By: Relevance
“…성을 검증한 연구들로는 정형외과 단위 연구 (Kim, 2005;Kwon & Park, 2002), 내과계 외과계 병동과 중환자실 단위 연구 (Park & Jung, 2005), 회복실 단위의 연구 (Kwon, 2006;Lee, 2000), 응급실 단위의 연구 (Oh, 2006), 신생아실 단위 의 연구 (Kim, 2004), 정신과 간호단위의 연구 (Choi, Kim, & Park, 2003), 수술실 단위의 연구 (Lee & Park, 2002), 중환 자실 단위의 연구 (Park, 2001), 혈액투석 단위의 연구 (Choi, 2001), 말기 암 환자 (Choi & Jang, 2005), 가정간호 대상 (Yong, Yoo, & Yoo, 2000 (Table 3) (Table 5). Health system 4 (2.2) Health system mediation 4 (2.…”
Section: 이러한 간호중재분류체계(Nic)를 국내에 적용하고 타당unclassified
“…성을 검증한 연구들로는 정형외과 단위 연구 (Kim, 2005;Kwon & Park, 2002), 내과계 외과계 병동과 중환자실 단위 연구 (Park & Jung, 2005), 회복실 단위의 연구 (Kwon, 2006;Lee, 2000), 응급실 단위의 연구 (Oh, 2006), 신생아실 단위 의 연구 (Kim, 2004), 정신과 간호단위의 연구 (Choi, Kim, & Park, 2003), 수술실 단위의 연구 (Lee & Park, 2002), 중환 자실 단위의 연구 (Park, 2001), 혈액투석 단위의 연구 (Choi, 2001), 말기 암 환자 (Choi & Jang, 2005), 가정간호 대상 (Yong, Yoo, & Yoo, 2000 (Table 3) (Table 5). Health system 4 (2.2) Health system mediation 4 (2.…”
Section: 이러한 간호중재분류체계(Nic)를 국내에 적용하고 타당unclassified
“…To date, the NIC has been implemented in nursing information systems at national, as well as international levels in order to describe and capture the interventions performed by nurses (Haugsdal & Scherb, ). Recent studies using the NIC in Korea were conducted in diverse nursing practice care settings (Oh et al ., ; Yong et al ., ; Kwon & Park, ; Lee & Park, ; Oh & Park, ; Choi et al ., ; Park & Jung, ; Cho & Kim, ; Hong et al ., ). All of these studies reported that the NIC is applicable for use in describing nursing practice in Korea.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, studies were conducted in more diverse care settings including: Intensive care units (Kim, 2008), adult medical surgical units (Kwon, 2002; Park, 2005), surgical recovery units (Kwon, 2006; Lee, 2000), pediatric inpatient settings (Kim, 2004; Oh, 2001), psychiatric care (Choi, Kim, & Park, 2003), and community care (Kim et al, 2006). The results of these studies support NIC use across diverse settings.…”
Section: Introductionmentioning
confidence: 99%